Improving the effectiveness of special physical training for personnel of the Ukrainian National Police using CrossFit - Marchenko , O.; Kholodova , O.; Vasetskyi , I. (Sportyvnyi Visnyk Prydniprovia, 2026)
Introduction and Purpose of the Study: This article examines key aspects of special physical training for personnel of the National Police of Ukraine in conditions of martial law. Within the framework of the study, practical recommendations for improving the special physical training of personnel of the National Police of Ukraine were developed and experimentally tested. Aim of the Study: To experimentally test the effectiveness of practical recommendations for improving the special physical training of personnel of the National Police of Ukraine. Materials and Methods: The study involved 20 employees of the National Police of Ukraine. A complex of methods was used to solve the set tasks: theoretical (content analysis of normative and program-methodological documents, comparative method of comparison and analysis of domestic experience on the studied problem); pedagogical (testing the level of physical fitness according to the following indicators: pull ups on the horizontal bar, running 100 m, running 3000 m); generally accepted methods of mathematical statistics. Results: It was determined that 68% of the studied have an average level of development of physical qualities, 22% – sufficient, and 10% of the studied contingent have a low level of development of physical qualities; practical recommendations for improving special physical training (SPT) of personnel of the National Police of Ukraine units were developed and experimentally tested using the CrossFit system, which is aimed at developing basic physical qualities, improving the functional capabilities of the body and improving professionally important qualities. Conclusions: It was found that the implementation of practical recommendations for improving the system of special physical training (SPT) of personnel of the National Police of Ukraine units using the CrossFit system (intensive strength functional training) led to a significant increase in the level of development of endurance, growth of strength indicators and improvement of speed qualities of respondents.